Efektivitas Senam Kebugaran untuk Peningkatan Kualitas Hidup pada Lansia di Posyandu Mawar Agung Desa Ceporan Kec.Gantiwarno Kab.Klaten - Suyamto Suyamto (Journal of Bionursing, 2022)
Elderlies registered at Posyandu Mawar Agung experienced various health problems. They reported increase uric acid with general complaints of joint pain, hypertension with complaints of frequent dizziness, stroke with complaints that all activities need help, rheumatism with complaints of swelling in the joints and pain when moving and sleep disturbances, from some of the health problems found that affect their daily activities. There is a demand for an elderly fitness exercise to reduce these health problems. This study examined the effect of fitness exercises on elderlies’ quality of life. The quasy experimental study was conducted to test the hypotheses. Total 118 elderlies registered at the Mawar Agung Posyandu, Ceporan Village, Gantiwarno Klaten`were invited. Pre post test with control group study design was applied. Results revealed that quality of life scores improved higher in experimental group than in control group. The imporved score gap between two groups was 6,08 ± 7,55 (p: 0.001) In conclusion, there was a significant scores discrepancy between experimental and control group. Fitnes gymnastic could improved quality of life of the Mawar Agung Posyandu. Helth educators were sugested to promote quality of life among elderlies in posyandu by fitnes exercises activities.